Program Analysis and Implementation of Rice Organic Farming System in Semarang Regency - Dwi Erlina Estuningtyas; Muniffatul Izzati; Hartuti Purnaweni (Diponegoro University, 2013)
The Republic of Indonesia Government through the Ministry of Agriculture has launched a program of “Go to Organic 2010” in order to accelerate the development of organic agriculture in some regions of Indonesia. This research aims to study the implementation of organic rice farming systems in District of Susukan, Semarang Regency. Specifically, the objectives of this study were (1) to analyze the program implementation of organic rice farming in the district of Susukan Semarang Regency, and (2) to evaluate the implementation of organic rice farming systems in terms of organic farming standards. The experiment was conducted in the Susukan District of Semarang Regency ranging from April to August 2013. Primary data were obtained from direct observations in the field using a questionnaire at predetermined sample area. Variables observed include correspondence between the implementation of organic rice farming in the community with organic farming criteria. The results showed that the farmers have implemented Organic Rice Farming Systems (ORFS) with a percentage of 83.3 percent and Conventional Farming Systems (CFS) 16.7 percent. The government has had a policy of organic rice farming, among others in the form of socialization in the development of organic rice farming and technical guidance in the development of organic rice farming. In general, community in the Susukan District of Semarang Regency has known environmentally farming of organic rice farming. In the rice farming community has grown organically and still need to be developed. Basically organic paddy cultivation in the district of Susukan District of Semarang Regency actually can not be said to be fully as organic rice farming, or more accurately called as semi-organic farming systems.